#### Answer

$y=x^2-12x+32$

#### Work Step by Step

We use the FOIL method. Then we simplify until the equation is in the form $y=ax ^2+bx+c$.
Hence: $y=(x-4)(x-8)=x^2-8x-4x+32=x^2-12x+32$

Published by
McDougal Littell

ISBN 10:
0618595414

ISBN 13:
978-0-61859-541-9

$y=x^2-12x+32$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.